Public engagement with MIST science. Issue 6 (1st December 2018) - Coxon, John; Sandhu, Jasmine; Provan, Gabby; Wild, Jim
Abstract : John Coxon, Jasmine Sandhu, Gabby Provan and Jim Wild summarize a meeting held in September. Abstract : John Coxon, Jasmine Sandhu, Gabby Provan and Jim Wild summarize the content and conclusions of the "Collaborative Public Engagement with MIST Science" meeting held in September.